Digital Certificate System for Verification of Educational Certificates Using Blockchain - Gayke, PS; Chennur, Jayesh; Muzzamil, Mulla; Joy, Jathin; Gosavi, Kunal (International Journal of Computer Sciences and Engineering, 2021)
In India Ministry of Education statistics, about one million graduates each year, some of them will goto countries, high schools or tertiary institutions to continue to attend, and some will be ready to enter the workplace employment. During the course of study, the students’ all kinds of excellent performance certificates, score transcripts, diplomas, etc., will become an important reference for admitting new schools or new works. As schools make various awards or diplomas, only the names of the schools and the students are input. Due to the lack of effective anti-forge mechanism, events that cause the graduation certificate to be forged often get noticed. In order to solve the problem of counterfeiting certificates, the digital certificate system based on block chain technology would be proposed. By the modifiable property of block chain, the digital certificate with anti-counterfeit and verifiability could be made. The procedure of issuing the digital certificate in this system is as follows. First, generate the electronic file of a paper certificate accompanying other related data into the database, meanwhile calculate the electronic file for its hash value. Finally, store the hash value into the block in the chain system. The system will create a related QR-code and inquiry string code to affix to the paper certificate. It will provide the demand unit to verify the authenticity of the paper certificate through mobile phone scanning or website inquiries. Through the modifiable properties of the block chain, the system not only enhances the credibility of various paper-based certificates, but also electronically reduces the loss risks of various types of certificate.